Effects of zero tillage and residue retention on soil quality in the mediterranean region of Northern Syria - Sommer, Rolf; Piggin, Colin; Feindel, David; Ansar, Muhammad; Delden, Lona van; Shimonaka, Kayoko; Abdalla, Jihad; Douba, Osama; Estefan, George; Haddad, Atef; Haj-Abdo, Rousheen; Hajdibo, Ali; et al. (Scientific Research Publishing, Inc., 2014)
Zero-tillage (ZT) and crop residue retention on the soil surface—two components of Conservation Agriculture (CA)—have been identified as promising management practices for sustainable agri- cultural intensification for some time. However, CA technology uptake by farmers in the dry areas of West Asia and North Africa (WANA) has yet to happen large-scale, even though the positive im- pact on yield has been demonstrated repeatedly. To explain the observed consistent increases in crop yield under ZT, a range of soil quality indicators were regularly monitored during 2008 to 2012 in the long-term ZT/CA trials at the headquarters of the International Center for Agricultural Research in the Dry Areas (ICARDA) in northern Syria. Results showed that CA had a positive im- pact on soil fertility. This was measurable by higher soil organic matter (SOM) and microbial bio- mass contents, increased levels of extractable phosphate, sometimes (but not always) higher amounts of larger water-stable soil aggregates, increased soil infiltration capacity and soil water retention. The buildup of SOM and associated carbon (C) sequestration was in the range of 0.29 Mg C/ha/yr, i.e. rather modest. High amounts of surface residues delayed the desiccation of the topsoil during the fallow period, but could not diminish the overall longer-term drying of the topsoil. The observed positive changes in soil quality were little, but nevertheless, in combination with the economic savings that ZT offers, this type of agricultural intensification provides an attractive op- tion for farmers in WANA, from the standpoints of economy and ecological efficiency.